The reproductive role, functions and methods of organizing associations of insurers - A. A. Tsyganov (Путеводитель предпринимателя, 2020)
The Russian insurer for almost the whole period of development of commercial insurance in our country do not feel protected, has been known to be the weaker party to the contract of insurance. It is important to strengthen the role of associations of insurers in the development of the insurance market.